Effect of Sex on Wasted Left Ventricular Effort Following Maximal Exercise - Lane, A. D.; Ranadive, S. M.; Yan, H.; Kappus, R. M.; Cook, M. D.; Sun, P.; Woods, J. A.; Wilund, K.; Fernhall, B. (International Journal of Sports Medicine, 2013)
Wasted left ventricular effort (∆Ew) refers to work required of the left ventricle to eject blood that does not result in increased stroke volume and is related to left ventricular hypertrophy. Literature shows that men and women have differing ventricular and vascular responses to and following exercise. Our purpose was to determine how ∆Ew changes post-exercise in men and women and examine potential mechanisms. We hypothesized a reduction in ∆Ew that would be greater in men and that central pulse wave velocity and wave intensity (WIA) would be related to ∆Ew. Blood pressures, central pulse wave velocity (cPWV), and WIA were obtained at rest, 15 and 30 min after maximal exercise. Both sexes reduced ∆Ew post-maximal exercise (p>0.05 for interaction), but women had higher ∆Ew at each time point (p<0.05). The first peak of WIA increased 15 min post-exercise only in women (p<0.05). cPWV was attenuated (p<0.05) in women at 15 min and men at 30 min (p<0.05) post-exercise with a significant time by sex interaction (p<0.05). WIA (1st peak) was correlated (p<0.05) to ∆Ew in both sexes before and 15 min post-exercise, but cPWV was only associated with ∆Ew in men at 30 min post-exercise. We conclude that both sexes decrease ∆Ew after maximal exercise, but vascular and ventricular changes associated with the attenuation of ∆Ew are not uniform between sexes.
Keywords: maximal exercise; sex differences; ventricular work